PENGARUH APLIKASI ASAM HUMAT DAN PUPUK NPK PHONSKA 15-15-15 TERHADAP SERAPAN NITROGEN DAN PERTUMBUHAN TANAMAN PADI SERTA RESIDU NITROGEN DI LAHAN SAWAH - Yulia Nuraini; Annisauz Zahro (Jurnal Tanah dan Sumberdaya Lahan, 2020)
The decline in lowland rice production can be caused by nitrogen nutrient loss through volatilization. The application of humic acid and Phonska 15-15-15 fertilizer can be a solution. This study aimed to determine the effect of humic acid and Phonska 15-15-15 fertilizer on nitrogen uptake by rice plant, rice plant growth, and nitrogen residues in paddy soils. The research used a randomized block design with 8 treatments and 3 replications. The treatments in this study included K (Control), A (Humic Acid 5 kg ha-1), P (Phonska fertilizer 240 kg ha-1), A1 (Humic Acid 1 kg ha-1 + Phonska 240 kg ha-1), A2 (Humic Acid 2 kg ha-1 + Phonska 240 kg ha-1), A3 (Humic Acid 3 kg ha-1 + Phonska 240 kg ha-1), A4 (Humic Acid 4 kg ha-1 + Phonska 240 kg ha-1), and A5 (Humic Acid 5 kg ha-1 + Phonska 240 kg ha-1). Â The parameters observed included nitrogen uptake in rice plants, rice plant growth, and nutrient residues in the soil. The results showed that humic acid and Phonska 15-15-15 fertilizer significantly affected N nutrient uptake, the highest effect was found in A3, which was 1.03 g plant-1 in 4 MST and 1.77 g plant-1 in 6 MST. Humic acid and NPK Phonska 15-15-15 fertilizer yielded the highest plant height at 4 MST and 6 MST was A3 treatment. The number of tillers at the age of 4 MST treatments gave the highest results, namely in the treatment of A3 and A4 as many as 3.33 tillers. At the age of 6 MST the treatment that gave the highest results was A3 treatment with 8 puppies. The nitrogen residues in the soil showed a significant effect where the highest residual yield in the soil was obtained from the A3 treatment of 0.23% as well as pH and C-organic respectively 6.69 and 3.10%.